ANALISIS PERBANDINGAN MAKNA KATA ONNA DAN JOSEI - , HIMAWAN GIRI PAWOKO, Wiwik Retno Handayani, S.S, M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research was conducted to describe the word onna dan josei that can be used to replace each other, the factors which influenced them, and the proper usage of the word based on the level of courtesy. The analysis used in this research requires the component of meaning from each words of onna and josei. To identify the components of meaning, we analyze the data which are sentences from novel and internet articles that contain the word onna and josei by performing three steps. The first step is by looking the arguments that accompany the word onna and josei as well as replacing the use of both words. The second step is to expand the sentence by adding an argument that doesnât exist in the sentence, such as an adverb on the left and right of the word onna and josei. The two steps described previously is used to determine the differences in meaning and nuances between the word onna and josei. The last step is to sort out the component of meaning that comes from the word onna and josei. The result from this research can be described into two main point. 1. The differences in meaning and nuances between onna and josei are determined by the members of its diagnostic component. 2. The factor that affect whether the word onna and josei is interchangeable or not, is the reference of the object that is described by the word onna and josei, and the speech circumstances that accompany the use of the word onna and josei.